Strengthening regional supply chains for agricultural transformation in Colombia - Peña, Y; Miller, V; Parra-Peña, Rafael Isidro; Lundy, Mark M. (2014)
Over the last 2 decades, Colombia has gained valuable experience in supporting agricultural supply chains. The government views this approach primarily as a means of achieving agricultural transformation, and to this end the Ministry of Agriculture and Rural Development (MADR, its Spanish acronym) has designed a set of innovative policies. Under these policies, regional committees plan and implement development initiatives in collaboration with the local public and private sectors. While achieving several notable successes, the committees have also come up against various challenges: boosting operational funds; developing stronger relationships with regional governments, private actors, and support systems; strengthening small-scale producer organizations; and, above all, creating a long-term regional vision for supply-chain development. Colombia must meet these challenges effectively if its public policies are to achieve the desired effect of enhancing agricultural productivity.